2017
DOI: 10.1186/s12958-017-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte polarized light microscopy, assay of specific follicular fluid metabolites, and gene expression in cumulus cells as different approaches to predict fertilization efficiency after ICSI

Abstract: BackgroundThe complex relationship between oocyte morphology, specific follicular fluid metabolites, gene expression in cumulus granulosa cells, and oocyte competence toward fertilization and embryo development still needs further clarification.MethodsForty-six oocytes retrieved from the largest pre-ovulatory follicle of patients undergoing intra-cytoplasmic sperm injection (ICSI) were considered assessing: (a) oocyte morphological characteristics at polarized light microscopy (PLM), (b) specific follicular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Our previous observations suggest that a MS of larger size is more frequently observed among women of advanced reproductive age and lower ovarian sensitivity to exogenous FSH, suggesting that the increased MS size could represent a marker of oocyte ageing, associated to maturation defects, causing fertilization failure or meiotic errors. Interestingly enough, we also reported that an increased MS size was associated with early embryo development arrest, before reaching the blastocyst stage [ 3 ]. Furthermore, the impact of female age on oocyte birefringent structures has been previously described and, in general, considered to be quite limited [ 3 , 51 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous observations suggest that a MS of larger size is more frequently observed among women of advanced reproductive age and lower ovarian sensitivity to exogenous FSH, suggesting that the increased MS size could represent a marker of oocyte ageing, associated to maturation defects, causing fertilization failure or meiotic errors. Interestingly enough, we also reported that an increased MS size was associated with early embryo development arrest, before reaching the blastocyst stage [ 3 ]. Furthermore, the impact of female age on oocyte birefringent structures has been previously described and, in general, considered to be quite limited [ 3 , 51 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, we also reported that an increased MS size was associated with early embryo development arrest, before reaching the blastocyst stage [ 3 ]. Furthermore, the impact of female age on oocyte birefringent structures has been previously described and, in general, considered to be quite limited [ 3 , 51 , 54 , 55 ]. In the present study, comparable maturation, fertilization, and cleavage rates were observed in the two groups, suggesting that in the analysed population the woman’s age may have exerted only a limited effect (if any) on oocyte quality and that the significant differences observed in the birefringent structures were likely to be related mainly to factors other than age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies linking the FF features with the respective oocyte fate in bovines have not been performed yet. Reports in humans have positively associated the presence of anti-Müllerian Hormone (AMH) in FF with competence of the respective oocyte [163,164], although with some contradictory results [165,166]. Conversely, a recent study that used a large population of transferred embryos matching FF samples indicated that AMH level in FF following withdrawal from the ovarian follicle is closely linked to the oocyte's competence and it is a suitable predictor of a live birth after single embryo transfer [167].…”
Section: Follicular Fluid Analysismentioning
confidence: 99%
“…Os outros dez miRNAs (miR-196a, miR-1225-3p, miR-1343-3p, miR-218, miR-23b-5p, miR-24, miR-760-5p, miR-455-3p, miR-483 (JOZWIK et al, 1999), os quais possuem maior competência a se desenvolver até o estágio de blastocistos (RIZOS et al, 2002) e, consequentemente de melhor qualidade. Esta enzima apresentou aumento significativo em fluido folicular associado a oócitos de menor competência, sugerindo uma maior necessidade de proteção antioxidante devido a um maior nível de dano oxidativo no FF de oócitos com baixo potencial de fertilização (REVELLI et al, 2017). O transcrito NOS2 é relacionado à resposta ao estresse oxidativo e senescência, quando comparadas células do cumulus entre mulheres jovens e mais velhas (MOLINARI et al, 2016), contudo, menos expresso em células do cumulus de melhor qualidade assim como neste estudo.…”
Section: Cnb X Blunclassified